( a − b ) 3 + ( b − c ) 3 + ( c − a ) 3 ( a 2 − b 2 ) 3 + ( b 2 − c 2 ) 3 + ( c 2 − a 2 ) 3
Simplify the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This solution essentially correct, but poorly presented
1. By making
a
,
b
,
c
do double duty, it is harder to understand the intention of your first line.
2. The numerator is not
a
2
−
b
2
+
b
2
−
c
2
+
c
2
−
a
2
=
0
Suggested presentation:
We know that if x + y + z = 0 , then x 3 + y 3 + z 3 = 3 x y z .
Consider x = a 2 − b 2 , y = b 2 − c 2 , z = c 2 − a 2 . This satisfies x + y + z = 0 , hence we can conclude that ( a 2 − b 2 ) 3 + ( b 2 − c 2 ) 3 + ( c 2 − a 2 ) 3 = 3 ( a 2 − b 2 ) ( b 2 − c 2 ) ( c 2 − a 2 ) .
Etc
( a − b ) ³ + ( b − c ) ³ + ( c − a ) ³ ( a ² − b ² ) ³ + ( b ² − c ² ) ³ + ( c ² − a ² ) ³ = 3 ( a − b ) ( b − c ) ( c − a ) 3 ( a ² − b ² ) ( b ² − c ² ) ( c ² − a ² ) =(a+b)(b+c)(c+a)
( a − b ) 3 + ( b − c ) 3 + ( c − b ) 3 ( a 2 − b 2 ) 3 + ( b 2 − c 2 ) 3 + ( c 2 − a 2 ) 3 = a 3 − 3 a 2 b + 3 a b 2 − b 3 + b 3 − 3 b 2 c + 3 b c 2 − c 3 + c 3 − 3 c 2 a + 3 c a 2 − a 3 a 6 − 3 a 4 b 2 + 3 a 2 b 4 − b 6 + b 6 − 3 b 4 c 2 + 3 b 2 c 4 − c 6 + c 6 − 3 c 4 a 2 + 3 c 2 a 4 − a 6 = − 3 a 2 b + 3 a b 2 − 3 b 2 c + 3 b c 2 − 3 c 2 a + 3 c a 2 − 3 a 4 b 2 + 3 a 2 b 4 − 3 b 4 c 2 + 3 b 2 c 4 − 3 c 4 a 2 + 3 c 2 a 4 = 3 ( − a 2 b + c a 2 + a b 2 − c 2 a − b 2 c + b c 2 ) 3 ( − a 4 b 2 + c 2 a 4 + a 2 b 4 − c 4 a 2 − b 4 c 2 + b 2 c 4 ) = a 2 ( c − b ) − a ( c 2 − b 2 ) + b c ( c − b ) a 4 ( c 2 − b 2 ) − a 2 ( c 4 − b 4 ) + b 2 c 2 ( c 2 − b 2 ) = a 2 ( c − b ) − a ( c + b ) ( c − b ) + b c ( c − b ) a 4 ( c 2 − b 2 ) − a 2 ( c 2 + b 2 ) ( c 2 − b 2 ) + b 2 c 2 ( c 2 − b 2 ) = ( a 2 − a c − a b + b c ) ( c − b ) ( a 4 − a 2 c 2 − a 2 b 2 + b 2 c 2 ) ( c 2 − b 2 ) = ( a ( a − c ) − b ( a − c ) ) ( c − b ) ( a 2 ( a 2 − c 2 ) − b 2 ( a 2 − c 2 ) ) ( c 2 − b 2 ) = ( a − b ) ( a − c ) ( c − b ) ( a 2 − b 2 ) ( a 2 − c 2 ) ( c 2 − b 2 ) = ( a − b ) ( a − c ) ( c − b ) ( a − b ) ( a + b ) ( a − c ) ( a + c ) ( c − b ) ( c + b ) = ( a + b ) ( a + c ) ( c + b ) = ( a + b ) ( b + c ) ( c + a )
Problem Loading...
Note Loading...
Set Loading...
Using : If a + b + c = 0 then a 3 + b 3 + c 3 = 3 a b c
We see that so for numerator a 2 − b 2 + b 2 − c 2 + c 2 − a 2 = 0 and for denominator we see a − b + b − c + c − a = 0 So the equation converts into 3 ( a − b ) ( b − c ) ( c − a ) 3 ( a 2 − b 2 ) ( b 2 − c 2 ) ( c 2 − a 2 ) This equation on factorising further simplifies to 3 ( a − b ) ( b − c ) ( c − a ) 3 ( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) which on cancelling common terms leaves us with ( a + b ) ( b + c ) ( c + a )